Comparative randomized study on the efficaciousness of endoscopic bipolar prostate resection versus monopolar resection technique. 3 year follow-up - Roberto Giulianelli (Archivio Italiano di Urologia e Andrologia, 2013)
Objective: Transurethral resection of the prostate (TURP) is the current optimal thera- py for the relief of bladder outflow obstruction, with subjective and objective success rate of 85 to 90%. Aim of this study was to evaluate efficacy and safety of Plasmakinetic ener- gy (Gyrus electro surgical system), which produces vaporization of tissue immersed in isotonic saline against standard monopolar transurethral resection of the prostate. Methods: From January 2002 to April 2002, 160 consecutive patients, who had low urinary tract symptoms (LUTS) of benign prostatic hyperplasia (BPH) were enrolled in this study. Patients were randomised to undergo bipolar TURP (80 patients) or monopolar TURP (80 patients). Preoperative work-up was assessed by administering IPSS, IIEF-5 and Qol questionnaires. All patients were submitted to uroflowmetry, transrectal ultrasound (TRUS), post-voidal residual urine measurement and PSA determination. In the two groups, IPSS, IIEF-5 and Qol, uroflowme- try, TRUS, post-voidal residual urine measurement, PSA determination and number of reopera- tions were evaluated at 1, 3, 6, 12, 18, 24, 30 and 36 months follow up, and then every year. Furthermore, in both groups operative time, resected tissue weight and perioperative complica- tions were analysed. Total postoperative catheter time, total post-operative hospital stay, haemo- globin loss were also recorded in the two groups. Results: Comparative data on IPSS symptom score, IIEF-5, Qol, PSA, peak urinary flow rate and post-void residual urine volume were similar in the two groups but showed a significant improve- ment respect to baseline values. The postoperative haemoglobin levels, postoperative catheteri- zation time, hospital stay and 3-year overall surgical re-treatment-free rate were significantly better in the bipolar group. Conclusions: Bipolar TURP has a comparable outcome to standard monopolar TURP at short and medium term regard to subjective and objective outcome measurements. Its impact on blad- der outlet function is also similar to that of monopolar TURP. Improvement in IPSS, Qol index, IIEF-5, Qmax and post-void residual urine volume were comparable in both group denoting sim- ilar efficacy of the techniques.